FUNGSIONALISASI PASAL 44 KUHP DALAM PENYIDIKAN TINDAK PIDANA PEMBUNUHAN (SUATU RE-ORIENTASI & RE-EVALUASI MENUJU REFORMULASI) - Ohoiwutun, Y A Triana; Nugroho, Fiska Maulidian; Martua Samosir, Samuel Saut; Setiyoargo, Arief (Veritas et Justitia, 2019)
Uncertainty with regard to the proper implementation of Article 44 of the Criminal Code is to be discussed.  In legal practice, the existence of mental disorder in those who are accused of murder or homicide will be made dependent on the decision of psychiatrist (authorized to conduct forensic psychology or psychiatry). In the case that such mental disorder is determined to be existing during a pre-trial hearing, the court is under no obligation to order cessation of the criminal proceeding. It is noted that in a number of cases the decision to terminate investigation or cease court proceeding falls completely under the Judge discretionary power.  The author’s recommendation is that a reformulation of Art. 44 of the Criminal Code is in order.